The Influence of Brand Ambassador, Store Atmosphere, and Perceived Quality on the Purchase Decision of Skintific Products at Cantik Tulungagung Store - Zamroni, M. (International Journal of Business, Law, and Education, 2025)
This study aims to examine the influence of Brand Ambassador, Store Atmosphere, and Perceived Quality on the purchasing decisions of Skintific products such as cleansers, moisturizers, and sunscreen at the Tulungagung Beauty Store. The method used in this study is descriptive quantitative with a sample of 100 respondents from Skintific consumers. The sampling technique used was purposive sampling, considering the suitability of the sample. Data processing was conducted using IBM SPSS 25 software. Data analysis in this study included classical assumption tests (normality, multicollinearity), multiple linear regression analysis, and the coefficient of determination (R²). The conclusion of this study is that the variables Brand Ambassador, Store Atmosphere, and Perceived Quality are positively related to purchasing decisions and obtained an R-square value considered to represent the coefficient of determination of 0.720, meaning that 72.0% of purchasing decisions are influenced by Brand Ambassador and Store Atmosphere, while the remaining 28.0% are influenced by other variables not included in this study